Perbedaan latihan passing berpasangan dengan perubahan tinggi net berat bola terhadap kemampuan passing bawah - Kresnapati, Pandu (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2020)
The purpose of this study is to find out which is better between paired under passing exercises with changes in net height and under paired passing exercises with changes in ball weight. The method used in this research is the experimental method. The population of the study was 123 volleyball athletes Club Bina Taruna Semarang. The sampling technique uses purposive sampling that is sampling based on certain characteristics, characteristics, or characteristics. This study only examined a portion of the population with a total of 20 male athletes who were familiar with volleyball, especially underpasses. The instrument in this study was a Brady Wall Volley Test under volleyball passing test. The data obtained were analyzed using a different test (t-test). Based on the results of the study it can be concluded that there is a significant difference between under pairing passing exercises with changes in net height and under pairing passing exercises with changes in ball weight. In the experimental group who got under-passing exercises in pairs with changes in ball weight had better results when compared to the experimental group who got under-passing exercises with changes in net height.